Optimal operation of battery energy storage system for mitigating voltage fluctuation in microgrid using cuckoo search optimization - Keerachat Tantrapon (2020)
© 2019 IEEE. The main effect of renewable energy based distributed generation such as photovoltaic (PV) and wind energy, caused by the variability and intermittency of power generation on microgrid operation, is called 'Power fluctuation' and 'Voltage fluctuation The most fluctuation on PV is dependent on cloud movement and daily weather. Therefore, the battery energy storage system (BESS) is one of the popular solutions to accommodate and enhance the controllability of the microgrid. In this paper, the cuckoo search optimization (CSo) approach is developed to optimize the operation of the BESS, and the main objective is to mitigate the voltage fluctuation in the microgrid. CSO was implemented by m-file script in MATLAB, while the load flow evaluation was calculated in DIgSILENT PowerFactory. The Mae Sa Riang microgrid in Thailand was selected as a case study to demonstrate the effectiveness of the proposed method. The simulation results show that the optimal operation of the BESS using CSO is more effective in mitigating voltage fluctuation than the microgrid controller method.